Cisplatin adducts of DNA as precursors for nanostructured catalyst materials. Issue 10 (1st September 2020) - Englert, Klaudia; Hendi, Ruba; Robbs, Peter H.; Rees, Neil V.; Robinson, Alex P. G.; Tucker, James H. R.
Abstract : A new role for the well-known cisplatin–DNA reaction is reported in the form of a method to generate a catalytic nanomaterial containing individually positioned platinum atoms. Abstract : The synthesis and characterisation of novel metal-modified DNA precursors for fuel cell catalyst development are described. Material precursors in the form of metal–DNA complexes were prepared through the reaction of DNA with cisplatin at various loadings and spectroscopically tested to confirm the platinum binding mode and the degree of complexation. The surface morphology of the DNA–metal material was analysed by Scanning Transmission Electron Microscopy (STEM), which revealed the extent of platinum nanocluster formation, with low metal loadings leading to observation of individual platinum atoms. Electrochemical measurements showed a greater electrocatalytic activity for the hydrogen evolution reaction (HER) with increased platinum loadings, shifting the half wave potential, E 1/2, away from the glassy carbon limit towards that of a bulk Pt electrode. This is explained further by Tafel plots, from which a change in the mechanism of the apparent rate limiting step for proton reduction from a Volmer to a Heyrovsky mechanism is postulated as the platinum loading increases.